Supply Chain Management in Zhendong Pharmaceutical Company - Li, Yan (2011)
Medicines are special commodity related to people’s lives and health, therefore, pharmaceutical distribution is an industry affecting the national economy and the people's livelihood. With health care reform, changeable pharmaceutical policy and fiercely increasing competition in the medical industry, pharmaceutical distribution companies should improve their level of logistics operations and reduce overall logistics management costs in order to gain a leading position in the competition. In China, drug distributors plays roles in logistics, transportation, inventory management and information management services due to little professional third party pharmaceutical logistics provider. Shanxi Zhendong Medical Logistics Company is comprehensive pharmaceutical based business enterprises providing medical logistics and distribution service for more than 10,300 kinds of products. The network of this company covers more than 80 counties of whole Shanxi province, 7,200 small and medium sized hospitals and township health centers, drug superstore chains and community clinics, which become one of the most extensive coverage enterprises in Shanxi Province. Proper logistics performance evaluation and the use of advanced information technology management help pharmaceutical distribution business improve competitiveness. Through the evaluation of the company's logistics performance, can company understand the conditions of logistics operating, identify shortcomings of logistics operations, and then verify the pharmaceutical distribution business logistics performance management has a certain practical significance. Information technology application is the success of pharmaceutical companies’ expansion and management costs reducing. As a link company in pharmaceutical industry, pharmaceutical distribution enterprises are needed to establish a modern logistics than any other companies.